Legal regulation of domestic violence in Croatia - Sučević Radmila (Temida)
Family Law passed in 1998 introduced the term domestic violence for the very first time in Croatian legal system. Article 118 of this Code contains explicit ban of if violent behavior of a spouse or other adult family member. Violation of this ban is, according to the article 362, a misdemeanor, and the sanction is up to 30 days of imprisonment. Article 118 is placed under section of parental care, subsection is Protection of rights and welfare of a child and minors. Entering article regarding family violence into this section and connecting violent behavior only to a spouse or other adult family member is dangerous, because of possibility for restrictive interpretation of this article in practice and giving protection only to children. However, in practice, although the implementation of this law started late, in June 1999, police mostly intervene and protect victims of domestic violence in all cases, no matter if it is a family with or without children. From January 1st 2001 violent behavior in a family is provided as criminal offence (article 215 of the Criminal Code). Sanction for this offence is from three months up to three years of imprisonment.